The Influence of the Implementation of Accounting Information Systems, Performance-Based Budgeting Applications, and Performance Reporting Systems on the Performance Accountability of Sidoarjo Regency Government Agencies - Suhgrowardi Anggun Wardani; Santi Rahma Dewi (Universitas Muhammadiyah Sidoarjo, 2022)
Law No. 32 of 2004 and Law No. 33 of 2004 have changed the accountability or accountability of local governments from vertical accountability (to the central government) to horizontal accountability (to the community through DPRD). This study aims to re-examine the effect of the application of accounting information systems, performance-based budgeting, and performance reporting systems on the performance accountability of local government agencies. The object of this research is the performance accountability of local government agencies. The subjects in this study were 18 Local Government Organizations (ODP) in the government of Sidoarjo Regency. The data used in this study is primary data collected by survey method by distributing questionnaires. The sampling technique was carried out by purposive sampling method. Data collected from questionnaires sent to 90 respondents. The number that can be used for this research is 45 questionnaires while the other 45 are not returned. The test model used in this study is multiple linear analysis with the help of SPSS software. The results of this study indicate that the application of accounting information systems, implementation of performance-based budgeting, and performance reporting systems have a positive effect on the accountability of the performance of local government agencies.